2003
DOI: 10.1002/anie.200351312
|View full text |Cite
|
Sign up to set email alerts
|

Di(isopropylprenyl)borane: A New Hydroboration Reagent for the Synthesis of Alkyl and Alkenyl Boronic Acids

Abstract: The best of the old: The new hydroboration reagent 1 combines the selectivity of disiamylborane (2) with the reactivity towards carbonyls of allyl boranes 3. Conventional oxidative workup conditions are avoided, as facile hydrolysis in protic media provides the corresponding boronic acids with up to 99 % anti‐Markovnikov selectivities. A one‐pot hydroboration/Suzuki–Miyaura protocol adds to the synthetic value of 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 101 publications
(23 reference statements)
0
35
0
Order By: Relevance
“…Amine 2 was then subjected to a Snieckus hydroboration 8. The resulting boronic acid was quenched with potassium hydrogen fluoride to access the corresponding potassium alkenyltrifluoroborate 3 as a waxy solid.…”
Section: Resultsmentioning
confidence: 99%
“…Amine 2 was then subjected to a Snieckus hydroboration 8. The resulting boronic acid was quenched with potassium hydrogen fluoride to access the corresponding potassium alkenyltrifluoroborate 3 as a waxy solid.…”
Section: Resultsmentioning
confidence: 99%
“…Several potassium β-aminoethyltrifluoroborates have been prepared through the hydroboration of Nvinyl substrates with di(isopropylprenyl)borane (i-PP 2 BH) followed by treatment with KHF 2 [29], giving rise to aminoethylating reagents [30]. These regents were initially cross-coupled with a variety of aryl and heteroaryl bromides in good yields in the presence of PdCl 2 (dppf) • CH 2 Cl 2 (Scheme 16) [31].…”
Section: Cross-coupling Of Novel Organotrifluoroboratesmentioning
confidence: 99%
“…Substrates 22, with both electron-donating and electron-withdrawing groups on the phenyl ring, performed well in b-borylation reaction giving 88-92 % yield of pure anti-Markovnikov products 23, which are characteristic for uncatalyzed hydroborations. [27,28] (Table 8). It was observed that in this case P^P ligands enabled lower loadings and higher efficiency than monodentate phosphines like Ph 3 P. Surprisingly, a-methylstyrene and b-methylstyrene did not react under similar reaction conditions.…”
Section: Entrymentioning
confidence: 99%
“…In recent years new catalytic systems have evolved to address regioselectivity and enantioselectivity, common challenges of catalytic hydroboration, as well as issues associated with side reactions such as dehydrogenative borylation and alkene hydrogenation. [27,28] Nevertheless, the need of the substrate scope expansion from simple alkenes to electron deficient conjugated analogues triggered further developments in the field. This challenge was first addressed by Marder et al [29] who latter on discovered a transition metal catalyzed addition of diboron reagents [30] to vinylarenes and a,bunsaturated olefins.…”
mentioning
confidence: 99%